A literatura de cordel em Libras: semiótica e transcodificação - Santos, Irakitan Bernardino dos (2023)
This work intended to make a semiotic analysis of the course of the meaning of the twine's literature in Libras, produced by a deaf author, and the twine's literature in Libras, produced by a hearing author, in order to understand the transculturation procedures that occurred between the two cultures. As specific objectives, it studied the necessary elements for the construction of this literature and the influences received from oral literatures; raised twine's literature leaflets in Libras by deaf authors or transcoded from Portuguese to Libras by hearing authors; identified, in the works of these authors, the manual and non-manual expressive forms, which represent prosodic markings and the twine's literature narratives in Libras; analyzed the composition of twine’s literature in Libras; highlighted the signs used in the Cordel Surdo that show signs of interculturality, observing the linguistic performances of Libras in the form of a twine’s literature, with the visual-gestural language differential, but with the same social value of communication as the oral language . The corpus consisted of two literary texts, one in Libras, by a deaf author, and the other in Portuguese, by a hearing author, transcoded into Libras. Greimas (1977) Batista (1999) were the theorists used to analyze the course of meaning of the text, while Pais (1993) and Rastier (2005) served to establish the discussion about its cultural aspects. In addition, we studied other authors, scholars of twine’s literature, especially deaf literature. The methodology adopted was qualitative and descriptive. The results obtained lead to the fact that the signed string cannot follow the structure of the string in Portuguese with regard to prosody and rhyme. As a suggestion, we present the twine’s literature we produced in 2016 for SINALP, in which the prosodic elements in Sign Language are observed with stretching of hand configurations complemented with manual and non-manual expressions.